Clay jewelry making and social Media marketing for clay jewelry businesses: strategies for success in Banolata Refractory Limited - Sharmili, Noshin (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023